2014
DOI: 10.1590/s1806-66902014000300024
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meet characteristics of very young Angus x Nelore steers in the Agreste Potiguar region

Abstract: -This work aimed to evaluate the quantitative and qualitative characteristics of the carcass and meat of very young steers, ½ Red Angus x Nelore (NEL) and ¾ Red Angus x Nelore (RED). Fifty males were used, 25 from each genetic group, fed in feedlots from weaning (7 months) until reaching the age for slaughter (15 months). A difference was observed between the genetic groups for gains at weaning (158.57 kg NEL and 181.60 kg RED ) but the weight at slaughter showed no statistical differences (412.33 kg NEL and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The breed selected for this type of breeding system should be the one that best suits the climate and production reality of each region. As a complement to this, the use of heterosis (crosses) is an excellent way to unify Zebu characteristics (fertility, rusticity and adaptability) with the meat quality, precocity and carcass finish of European breeds, which produces animals of excellent performance for fattening in intensive systems (PEREIRA, 2012;FAÇANHA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breed selected for this type of breeding system should be the one that best suits the climate and production reality of each region. As a complement to this, the use of heterosis (crosses) is an excellent way to unify Zebu characteristics (fertility, rusticity and adaptability) with the meat quality, precocity and carcass finish of European breeds, which produces animals of excellent performance for fattening in intensive systems (PEREIRA, 2012;FAÇANHA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Crossbreeding of zebu cattle between European breeds has shown high performance in weight gain tests. Assessments between the Nellore and crossbred breeds have shown that there is a great difference between them, reaching several months at the age of slaughter, to achieve similar final carcass weight (PEREIRA, 2012;FAÇANHA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, os primeiros experimentos eram realizados para seleção de raças mais adaptadas às condições de criação brasileiras (EUCLIDES FILHO,1999). Silva (2008) FAÇANHA et al, 2014).…”
Section: Cruzamento Industrialunclassified